Correlation Between Mathematical Literacy Abilities and Students' Mastery of Problem Solving Abilities - Ma'ruf, Abdul Hakim; Triyono, Ageng; Riaseh, Arlita Gita; Nuary, Rusdi Hamdany; Permatasari, Nisa; Saleh, Rusmin R.M. (AlphaMath : Journal of Mathematics Education, 2024)
This research aims to determine whether or not mathematical literacy skills influence students' problem-solving abilities. The research method used is quantitative research with a regression approach. The subjects were 64 class XI students, who were selected using cluster random sampling from a population of 133 students. Data was obtained using the Mathematical Literacy Ability Questionnaire and Mathematical Problem Solving Ability Test Instrument. Data were analyzed using appropriate test statistics, namely the Chi-Square and Simple Linearity Test as prerequisite tests. Hypothesis testing is carried out in stages: (1) Pearson's Product Moment Correlation analysis, (2) Correlation Significance Test, and (3) Coefficient of Determination Test. After the data analysis, it was concluded that mathematical literacy abilities (X) positively influenced mathematical problem-solving skills (Y). This is proven by the calculation results of Sig.=0.000 < Sig.Î± =0.05 and the coefficient of determination value of 0.906. This means that mathematical literacy skills strongly influence mathematical problem-solving abilities, and the effect is 90.6%. The regression equation Y = -53.813 + 0.8189X shows that for every additional unit of variable X, the Y value or students' mathematical problem-solving ability increases by 0.8189.